Location of contact residues in pharmacologically distinct drug binding sites on P-glycoprotein - Mittra, Rituparna; Pavy, Megan; Subramanian, Nanditha; George, Anthony M.; O'Mara, Megan L.; Kerr, Ian D.; Callaghan, Richard (Elsevier, 2017)
The multidrug resistance P-glycoprotein (P-gp) is characterised by the ability to bind and/or transport an astonishing array of drugs. This poly-specificity is imparted by at least four pharmacologically distinct binding sites within the transmembrane domain. Whether or not these sites are spatially distinct has remained unclear. Biochemical and structural investigations have implicated a central cavity as the likely location for the binding sites. In the present investigation, a number of contact residues that are involved in drug binding were identified through biochemical assays using purified, reconstituted P-gp. Drugs were selected to represent each of the four pharmacologically distinct sites. Contact residues important in rhodamine123 binding were identified in the central cavity of P-gp. However, contact residues for the binding of vinblastine, paclitaxel and nicardipine were located at the lipid-protein interface rather than the central cavity. A key residue (F978) within the central cavity is believed to be involved in coupling drug binding to nucleotide hydrolysis. Data observed in this investigation suggest the presence of spatially distinct drug binding sites connecting through to a single translocation pore in the central cavity.